# PROVE THAT PROBLEMS IN DIFFERENTIATION

## About "Prove that Problems in Differentiation"

Prove that Problems in Differentiation :

Here we are going to see how to solve prove that problems in differentiation.

## Prove that Problems in Differentiation - Examples

Question 1 :

Differentiate the following

If u = tan-1 [√(1+x2) - 1]/x and v = tan-1x, find du/dv

Solution :

v = tan-1x

x  =  tan v

u = tan-1 [√(1+tan2v) - 1]/tan v

u = tan-1 [√(sec2v) - 1]/tan v

u = tan-1 [sec v - 1]/tan v

By applying sec v = 1/cos v and tan v = sin v / cos v

u = tan-1 ((1 - cos v)/sin v)

u = tan-1 ((2sin2 (v/2))/2sin (v/2) cos (v/2))

u = tan-1 ((sin (v/2)/cos (v/2))

u = tan-1 (tan (v/2))

u = v/2

du/dv  =  1/2

Question 2 :

Find the derivative with tan-1 (sin x/(1 + cos x)) with respect to tan-1 (cos x/(1 + sin x))

Solution :

Let u = tan-1 (sin x/(1 + cos x))

u  =  tan-1 [(2 sin (x/2) cos (x/2)/(2 cos2 (x/2))]

=  tan-1 [(sin (x/2) /(cos (x/2)]

=  tan-1 (tan (x/2))

u = x/2

du/dx  =  1/2    ------(1)

Let v  =  tan-1 (cos x/(1 + sin x))

v  =  tan-1 (sin (π/2 - x)/(1 + cos (π/2 - x))

By applying the trigonometric formula for sin x and 1 + cos x, we get

v  =  tan-1 (sin (π/2 - x/2)/cos (π/2 - x/2))

v  =  tan-1 (tan (π/2 - x))

v  =  (π/2 - x/2)

dv/dx  =  -1/2   ------(2)

From (1) and (2), we have to find the value of du/dv

(1)/(2)  ==>  (1/2) / (-1/2)

=  -1

Question 3. :

If y = sin-1x then find y''

Solution :

y = sin-1x

y'  =  1/√(1 - x2

√(1-x2)  (y')  =  1

√(1-x2)  (y'') + y' (1/2√(1-x2))(-2x)  =  0

√(1-x2)  (y'') + y' (-x/√(1-x2))  =  0

((1-x2)  (y'') - y' x)/√(1-x2)  =  0

(1-x2)  (y'') - y' x  =  0

y''  =  xy'/(1-x2)

y''  =  xy'/(1-x2)

By applying the value of y', we get

y''  =  x( 1/√(1 - x2))/(1-x2)

y''  =  x/(1 - x2)3/2

Question 4 :

If y = e^(tan-1x) show that (1+ x2 ) y'' + (2x −1) y' = 0 .

Solution :

y = e^(tan-1x)

log y  =  tan-1x

(1/y)y'  =  1/(1+x2)

y'  =  y/(1+x2)

y''  =  [(1 + x2)y' -  y(2x)] / (1+x2)2

(1+x2)y''  =  [(1 + x2)y' -  y(2x)]

By dividing (1 + x2) on both sides, we get

(1+x2) y''  =  y' - 2xy/(1+x2)

(1+x2) y''  =  y' - 2xy'

(1+x2) y''  =  y'(1 - 2x)

(1+x2) y''  =  - y'(2x - 1)

(1+x2) y'' + y'(2x - 1)   =  0

Hence proved.

After having gone through the stuff given above, we hope that the students would have understood, "Prove that Problems in Differentiation"

Apart from the stuff given in "Prove that Problems in Differentiation", if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

## Recent Articles

1. ### SAT Math Videos

May 22, 24 06:32 AM

SAT Math Videos (Part 1 - No Calculator)

2. ### Simplifying Algebraic Expressions with Fractional Coefficients

May 17, 24 08:12 AM

Simplifying Algebraic Expressions with Fractional Coefficients